The Road Home : A Novel - Lewis, Beverly 1949- (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2018)
Sent from Michigan to Pennsylvania, Lena Rose Schwartz grieves the death of her Amish parents and the separation from her siblings as well as her beau, Hans Bontrager. She longs to return home to those she loves most. However, she soon discovers that Lancaster County holds charms of its own.
Keywords: Amish women -- Fiction; Amish -- Fiction; Grief -- Fiction; Homesickness -- Fiction; Amish Country (Pa.) -- Fiction; Religious fiction; Romance fiction